2018
DOI: 10.31219/osf.io/ezg2j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Free will, determinism, and intuitive judgments about the heritability of behavior

Abstract: The fact that genes and environment contribute differentially to variation in human behaviors, traits and attitudes is central to the field of behavior genetics. Perceptions about these differential contributions may affect ideas about human agency. We surveyed two independent samples (N = 301 and N = 740) to assess beliefs about free will, determinism, political orientation, and the relative contribution of genes and environment to 21 human traits. We find that lay estimates of genetic influence on these trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 22 publications
1
26
1
1
Order By: Relevance
“…Considering the more inactive items IGA1 and IGA2 when compared to items IGA3 (genes and environment in equal parts) and IGA4 (Figure 1), we found similarity with the study of Cástera and Clément (2014) which found that the higher the number of years in the graduation, the smaller was the level of genetic determinism of the evaluated teachers. Another group that understood the interaction between genes and environment is educated mothers with schooling and with more than one child (Willoughby et al, 2019). Still comparing the present study with the aforementioned study, knowledge in biology did not influence beliefs in innatism (Castéra & Clément, 2014).…”
Section: Teachers' Perception About Intelligencecontrasting
confidence: 46%
See 4 more Smart Citations
“…Considering the more inactive items IGA1 and IGA2 when compared to items IGA3 (genes and environment in equal parts) and IGA4 (Figure 1), we found similarity with the study of Cástera and Clément (2014) which found that the higher the number of years in the graduation, the smaller was the level of genetic determinism of the evaluated teachers. Another group that understood the interaction between genes and environment is educated mothers with schooling and with more than one child (Willoughby et al, 2019). Still comparing the present study with the aforementioned study, knowledge in biology did not influence beliefs in innatism (Castéra & Clément, 2014).…”
Section: Teachers' Perception About Intelligencecontrasting
confidence: 46%
“…A specific sample for teachers of twin 7-year-olds, considering a Likert scale, where number one represents genetic influence and number five, environmental influence, generated an average of 2.35 (Walker & Plomin, 2005); the teacher sample of the present study, with different analysis, in a previously reported result, generated an average of 2.57. In an inverted scale, participants at least 18 years old and located in the United States had averages from 3.32 to 3.37 (Willoughby et al, 2019). The exception to the pattern found so far is given in a sample of Brazilian university students, which generated an average of 2.61, also with an inverted scale, in which lower averages represent greater environmental influence for intelligence (Gericke et al, 2017).…”
Section: Public Perceptions About Human Cognitionmentioning
confidence: 74%
See 3 more Smart Citations